Optimalisasi Manajemen Persediaan Bahan Baku melalui Metode EOQ pada UMKM Sambal Valir - Leonardo Ahmadani, Zardan (Atma Workshop Innovation, 2025)
This study analyzes the impact of raw material price fluctuations on production costs and selling prices, while evaluating the effectiveness of inventory management strategies using the Economic Order Quantity (EOQ) method in the case of the UMKM Sambal Valir. Employing a qualitative intrinsic case study approach, data were collected through in-depth interviews, observation, and documentation involving the business owner, consumers, and two competitors (Dapur Sabil and Auko Lauk). The findings reveal that the volatility of key raw materials, particularly chili and cooking oil, has a direct effect on price stability and production efficiency. The application of EOQ proved effective in reducing ordering and holding costs, minimizing the risk of overstocking or stockouts, and supporting more adaptive production planning. Furthermore, the study emphasizes the importance of understanding consumer behavior and demand patterns in determining optimal order quantities and frequencies. These results highlight that an EOQ-based inventory strategy not only enhances cost efficiency but also strengthens the competitiveness of small and medium enterprises in navigating raw material market volatility